2019
DOI: 10.3389/fpls.2019.01110
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Pentaploid Crosses for the Introgression of Amblyopyrum muticum and D-Genome Chromosome Segments Into Durum Wheat

Abstract: The wild relatives of wheat provide an important source of genetic variation for wheat improvement. Much of the work in the past aimed at transferring genetic variation from wild relatives into wheat has relied on the exploitation of the ph1b mutant, located on the long arm of chromosome 5B. This mutation allows homologous recombination to occur between chromosomes from related but different genomes, e.g. between the chromosomes of wheat and related chromosomes from a wild relative resulting in the generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Chromosomes 4T-b and 4H ch from Am. muticum or H. chilense were also transferred into durum wheat, resulting in the development of 4T-b(4B) and 4H ch (4B) disomic substitution lines, respectively (Calderón et al, 2012 ; Othmeni et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromosomes 4T-b and 4H ch from Am. muticum or H. chilense were also transferred into durum wheat, resulting in the development of 4T-b(4B) and 4H ch (4B) disomic substitution lines, respectively (Calderón et al, 2012 ; Othmeni et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its lower planting area compared with hexaploid wheat, the global durum wheat production has been forecast up to 42.7 million tons (MT) in 2020–2021 (Agriculture Agri-Food Canada, 2021 ). About 75% of the global durum wheat production is contributed by the Mediterranean region (Othmeni et al, 2019 ), where crops are mainly grown under environmental (high temperature, drought, and salinity) and biotic (pests and diseases) stresses (Tidiane Sall et al, 2019 ). In China, durum wheat cultivation was first started in the 1970s using varieties introduced from European countries such as Italy (Zhao et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each KASP TM assay, two allele-specific primers and one common primer were used ( Supplementary Table S1). Genotyping reactions were performed as described in Othmeni et al (2019) using a ProFlex PCR system (Applied Biosystems by Life Technology). A final reaction volume of 5 µl was used which included 1 ng genomic DNA, 2.5 µl KASP reaction mix (ROX), 0.068 µl primer mix and 2.43 µl nuclease free water.…”
Section: Genotyping With Kasp Markersmentioning
confidence: 99%
“…In situ hybridization easily enables the visualization of chromosomal introgressions from one genome into another using labelled genomic DNA from the donor species as probe. Previous studies have showed the identification of the genome of related species by chromosomal introgression lines using FISH or GISH in a wheat genetic background 15 17 . In addition to wheat, these cytogenetic studies are possible in other species 18 20 .…”
Section: Introductionmentioning
confidence: 99%